Evolution of elastic behavior of alite paste at early hydration stages. Issue 11 (17th July 2020) - Huang, Tingjie; Yuan, Qiang; Zuo, Shenghao; Shi, Caijun
Abstract: Elastic behavior is an important aspect of fresh cement‐based materials. In this paper, the elasticity development of fresh pure alite paste within 5 hours was monitored in situ by small amplitude oscillation shear. Isothermal microcalorimetry, X‐ray diffraction, scanning electronic microscopy, 1 H nuclear magnetic resonance, zeta potential measurements were used to investigate the underlying mechanisms. It was found that the evolution of storage modulus can be characterized by three different stages. The first stage stems from the compression of electrical double layer and the slight increase of solid volume fraction; the second stage is only controlled by the colloidal interaction; and the third stage is associated to the significant growth of solid volume fraction, the enhancement of short‐range attraction and the rigidification of calcium silicate hydrate (CSH) network. Moreover, the relationship between the formation of CSH and the growth of elasticity was also quantified.